Enhanced Optical and Infrared Activity of Nanosphere Dimers Attributed to Dimer Geometry - D. Keith Roper; Jin-Woo Kim; Ricardo R. Romo; Joseph Batta-Mpouma (IEEE Open Journal of Nanotechnology)
Enhanced optical and infrared activity of subwavelength metal nanoparticles is key to their use in optoelectronics, spectroscopy, and sensing. The present work compared spectra of nanosphere dimers merged by centrifuging gold nanospheres with corresponding simulated nanoscale dimers. Geometric features of the nanosphere dimers were related to corresponding optical and near-infrared activity through simulation. Differences in optical and infrared activity of the nanosphere dimers were largely attributable to changes in the radius of the nanosphere and the radius of the conductive junction between merged nanospheres. The features observed in the experimental spectra were attributed to a select number of dimers exhibiting predominantly optical and infrared activity, consistent with observations made in the corresponding transmission electron microscope image. The preparation and simulation methods in the present work appear useful to guide design, fabrication, and implementation of sustainably-synthesized nanosphere dimers with desired optical features for optoelectronic, spectroscopic, and sensing applications.